Does liming grasslands increase biomass productivity without causing detrimental impacts on net greenhouse gas emissions?. (1st May 2022) - Abdalla, Mohamed; Espenberg, Mikk; Zavattaro, Laura; Lellei-Kovacs, Eszter; Mander, Ulo; Smith, Kate; Thorman, Rachel; Damatirca, Claudia; Schils, Rene; ten-Berge, Hein; Newell-Price, Paul; Smith, Pete
Abstract: Soil acidification has negative impacts on grass biomass production and the potential of grasslands to mitigate greenhouse gas (GHG) emissions. Through a global review of research on liming of grasslands, the objective of this paper was to assess the impacts of liming on soil pH, grass biomass production and total net GHG exchange (nitrous oxide (N2 O), methane (CH4 ) and net carbon dioxide (CO2 )). We collected 57 studies carried out at 88 sites and covering different countries and climatic zones. All of the studies examined showed that liming either reduced or had no effects on the emissions of two potent greenhouse gases (N2 O and CH4 ). Though liming of grasslands can increase net CO2 emissions, the impact on total net GHG emission is minimal due to the higher global warming potential, over a 100-year period, of N2 O and CH4 compared to that of CO2 . Liming grassland delivers many potential advantages, which justify its wider adoption. It significantly ameliorates soil acidity, increases grass productivity, reduces fertiliser requirement and increases species richness. To realise the maximum benefit of liming grassland, we suggest that acidic soils should be moderately limed within the context of specific climates, soils and management. Graphical abstract: Responses of grass dry matter production to liming in the different climatic zones (a), number of species (b), soil types (c) and amounts of fertilisation (d). Effect size stands for the response ratio between treatment and control. Bars represent the 95% confidence intervals. The number of observations of each variable is noted beside the bar. Response ratio ±95% confidence intervals do not overlap 0 means p < 0.05. Image 1 Highlights: Liming grasslands either reduced or had no effects on N2 O and CH4 emissions. The impact of liming grasslands on total net GHG emission is minimal. Liming grasslands significantly ameliorates soil acidity. Liming increases grass productivity, reduces fertiliser requirement and increases species richness. Acid soils should be moderately limed within the context of specific climates, soils and management.